1981
DOI: 10.1007/bf00896366
|View full text |Cite
|
Sign up to set email alerts
|

Parental death or divorce and the school adjustment of young children

Abstract: This study examined the effects of two potentially crisis-producing experiences, parental divorce or death, on the school adjustment of young children. Children with such "crisis" histories were found to show greater overall school maladaptation than children without such histories. Children of divorce had significantly more acting-out problems than noncrisis controls or death children and those with histories of parental death more serious shy-anxious problems than the other groups. These effects were stable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0
6

Year Published

1982
1982
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 24 publications
1
22
0
6
Order By: Relevance
“…For example, the family crisis model suggests that psychological distress, emotional resentment, and social tension are more commonly associated with parental divorce and separation than parental death (e.g., Biblarz & Raftery, 1999;Chen & Kaplan, 1997;Wadsworth, 1979;Wells & Rankin, 1986). Furthermore, it has been suggested that children experiencing such crisis events often respond by seeking attention, "acting out," or engaging in diversionary tactics that involve antisocial behaviors (Felner et al, 1981). In other words, youth who experience parental divorce or separation may feel resentment toward their parents that will, in turn, increase the likelihood of weak family attachment and participation in delinquent activities.…”
Section: Family Crisis Modelmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, the family crisis model suggests that psychological distress, emotional resentment, and social tension are more commonly associated with parental divorce and separation than parental death (e.g., Biblarz & Raftery, 1999;Chen & Kaplan, 1997;Wadsworth, 1979;Wells & Rankin, 1986). Furthermore, it has been suggested that children experiencing such crisis events often respond by seeking attention, "acting out," or engaging in diversionary tactics that involve antisocial behaviors (Felner et al, 1981). In other words, youth who experience parental divorce or separation may feel resentment toward their parents that will, in turn, increase the likelihood of weak family attachment and participation in delinquent activities.…”
Section: Family Crisis Modelmentioning
confidence: 96%
“…2 Following earlier research, the present article refers to four of these paradigms as social control theory, the social control/parental absence model (see Amato & Keith, 1991;Demuth & Brown, 2004), the family crisis model (see Biblarz & Raftery, 1999;Chen & Kaplan, 1997;Felner, Ginter, Boike, & Cowen, 1981;Wells & Rankin, 1986), and the economic strain model (see Amato & Keith, 1991;Biblarz & Raftery, 1999). Each framework provides insight on how family type, family processes, and structural factors contribute to, or increase the opportunity for, juvenile delinquency.…”
Section: Theoretical Backgroundmentioning
confidence: 98%
“…In fact, approximately 50% of children who lose a parent are noticeably impaired in their everyday functioning during the first year of bereavement (Black, 1978). Bereaved children ages 3-6, as well as those in elementary school, showed elevated levels of depression, anxiety, and behavior problems (Kranzler, Shaffer, Wasserman, & Davies, 1990;Felner, Ginter, Boike, & Cowen, 1981). Loss of a sibling is believed to be very difficult for a child as well, often attributed to the fact that parents who have lost a child may become emotionally unavailable.…”
Section: Childhood Grief and Lossmentioning
confidence: 99%
“…Prior literature has demonstrated that parental divorce may be associated with increased risk for dysfunction in children (Felner, Ginter, Boike, & Cowen, 1981;Felner, Stolberg, & Cowen, 1975;Hretherington, Cox, B Cox, 1978;Jacobson, 1978aJacobson, ,, 1978b; however, parental divorce may also provide a positive solution to a destructive family situation by serving to alleviate the chronic stress experienced by children in families where there are heightenled levels of discord and conflict (Emery, 1982;Felner, 1985). Thus, if the tasks of family reorganization that accompany divorce are adequately mastered, this transition may provide the opportunity to reverse or forestall the development of maladaptive behaviors in children rather than lead to increased risk for dysfunction (Felner, 1985;Felner et al, 1983).…”
mentioning
confidence: 96%